ChemInform Abstract: Iridium Catalyzed Carbocyclizations: Efficient (5 + 2) Cycloadditions of Vinylcyclopropanes and Alkynes. Issue 23 (June 2015) - Melcher, Michaela‐Christina; von Wachenfeldt, Henrik; Sundin, Anders; Strand, Daniel
Abstract The first examples of iridium‐catalyzed inter‐ and intramolecular vinylcyclopropane—alkyne (5+2) cycloadditions are reported.